1996
DOI: 10.1016/s0006-3495(96)79293-7
|View full text |Cite
|
Sign up to set email alerts
|

Myosin light chain phosphorylation affects the structure of rabbit skeletal muscle thick filaments

Abstract: To identify the structural basis for the observed physiological effects of myosin regulatory light chain phosphorylation in skinned rabbit skeletal muscle fibers (potentiation of force development at low calcium), thick filaments separated from the muscle in the relaxed state, with unphoshorylated light chains, were incubated with specific, intact, myosin light chain kinase at moderate (pCa 5.0) and low (pCa 5.8) calcium and with calcium-independent enzyme in the absence of calcium, then examined as negatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
149
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(165 citation statements)
references
References 40 publications
13
149
2
1
Order By: Relevance
“…One mechanism proposed to explain the results presented here is that phosphorylation of myosin prevents the binding of myosin heads to the core of the thick filament, forming an ordered array (Levine et al 1996). The inability of myosin heads to lie in this configuration means that heads are more able to interact with actin thus generating a population of heads in non-force generating states.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…One mechanism proposed to explain the results presented here is that phosphorylation of myosin prevents the binding of myosin heads to the core of the thick filament, forming an ordered array (Levine et al 1996). The inability of myosin heads to lie in this configuration means that heads are more able to interact with actin thus generating a population of heads in non-force generating states.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast phosphorylation of myosin causes disruption of the ordered array, increasing the fraction of myosin heads in a disordered configuration in the space around the thick filament, see Fig. 9 ( Levine et al 1996), which means that these heads can more readily bind with actin in non-force generating states, State 3 in Fig. 9.…”
Section: The Mechanism Of Phosphorylation Induced Inhibition Of Velocitymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, studies by Levine and colleagues using permeabilized rabbit psoas muscle fibres showed that phosphorylation of the RLC reversibly disrupts the normally well-ordered, helical arrangement of myosin heads close to the surface of the thick filament (Levine et al, 1996;Levine et al, 1998). Sweeney and colleagues showed that this disruption was due to charge repulsion between the myosin head and the thick filament, as the addition of a negative charge to the RLC mimicked this effect of phosphorylation (Sweeney et al, 1994).…”
Section: Molecular Mechanism For Speed and Direction Dependencementioning
confidence: 99%